Awareness through Training Programs among Sericulture Entrepreneurs of weaker sections- a study in Anantapur district of Andhra Pradesh - Seshagiri, S.V.; Raju, P.J. (Journal of Agricultural Extension Management, 2019)
Agriculture based Sericulture industry can be seen as an effective socioeconomic tool for inclusive growth and for creation of gainful employment to the rural and unemployed youth which helps to uplift the socio-economic status of small and marginal farmers. Compared to agricultural crops, sericulture provides round the year employment and higher income to the rural entrepreneurs. Most of the families in silk industry practice it traditionally without undergoing any specific skill development training programme. As a result, farmers lose their crops and even with lesser cocoon yield, the crop stability and quality is not assured. To make it a more viable, economic and profitable enterprise skilled / trained human resource is very essential. Training provides a systematic improvement in knowledge and skills which in turn helps the trainees to function effectively and efficiently in their given task. The feedback from training organised especially for weaker sections in Anantapur district of Andhra Pradesh covering 211 farmers suggests that the training was quite useful for the farmers in mulberry cultivation and rearing of silkworms on scientific lines to ensure successful crops with higher yield.